2017
DOI: 10.1002/adfm.201702618
|View full text |Cite
|
Sign up to set email alerts
|

Bjerknes Forces in Motion: Long‐Range Translational Motion and Chiral Directionality Switching in Bubble‐Propelled Micromotors via an Ultrasonic Pathway

Abstract: Manipulation of a micromotor's locomotion has been the ultimate aim of scientists and engineers alike. While numerous roadmaps have been cast, the interswitching of the locomotion and directionality of these miniaturized machines remains elusive. In this report, ultrasound is utilized to produce stop/go motion on bubble‐propelled micromotors via Bjerknes forces. An intricate study using high‐speed camera on the interactions between the bubbles and micromotor is undertaken. The reciprocal action between oscilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 61 publications
0
20
0
1
Order By: Relevance
“…On the other hand, the assembly and disassembly of the acoustic microrobots would be possible, due to the mutual multibubble interactions resulting from the secondary order Bjerknes force (34,50). In addition to the actuation and control strategies, the real-time imaging of the microscopic swimmers presents a grand challenge in the microrobotics field.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the assembly and disassembly of the acoustic microrobots would be possible, due to the mutual multibubble interactions resulting from the secondary order Bjerknes force (34,50). In addition to the actuation and control strategies, the real-time imaging of the microscopic swimmers presents a grand challenge in the microrobotics field.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, unlike thermal or optical stimuli, this approach does not affect the fuel or reaction rate allowing for maintaining chemical propulsion integrity. More recent studies have shown that apart from ON/OFF motion, the ultrasound fields can induce oscillations of bubble aggregates and hinder the bubble forming phenomena of the microrocket, resulting in change of directionality …”
Section: Multistimuli‐enabled Advanced Motion Controlmentioning
confidence: 99%
“…This situation might correspond to a situation observed experimentally, where the bubble exits from both the rear and front openings, spoiling a robust unidirectional motion [15,29]. This mechanism might even be exploited to achieve complex bidirectional motions, as described in [30] as an alternative strategy to the ultrasound control [31]. In fact, when the bubble exits from the front opening, the micro-rocket displaces from left to right while it displaces from right to left when the bubble exits from the rear opening.…”
Section: Critical Threshold For Sustained Bubble Ejectionmentioning
confidence: 81%